Differences in the Use of Rice Husk Bedding and Slat-Bedding on Broiler Chicken Performance in Closed House Cages - Sidik, Doadan Syahril; Wahyu Mulyono, Ali Mursyid; Husein, Muhammad (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2025)
Bedding type is one of the factors that affect broiler chicken performance. Researchers use this as a basis for testing the differences in the use of rice husk and slat cage bedding on the performance of broiler chickens in closed cages. This study used a quantitative approach with a comparative design to analyze the differences between two independent groups. This study used a quantitative approach with a comparative design to compare two independent groups. Twelve thousand broiler chickens were used, with 6,000 in slat bedding cages and 6,000 in rice husk bedding cages; each group was divided into three replications. In each replication, a sample of 20 chickens was taken. The parameters observed were Feed Intake (FI), Body Weight Gain (BWG), and Feed Conversion Ratio (FCR). The data obtained were explained using the Independent sample T-Test method. Data were taken in 1 maintenance period in a closed-house cage. Based on the statistical analysis obtained, the FI data was significantly different, namely (Sig. 0.006), the average feed consumption on the slat bedding cage showed higher results compared to rice husk bedding, as well as PBB (Sig. 0.001) and FCR (Sig. 0.034). Based on the results of this study, it can be concluded that slat bedding in close house cages affects consumption, weight gain, and feed conversion better than rice husk bedding.